2008
DOI: 10.1038/eye.2008.362
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative retinal vascular calibre changes in diabetes and retinopathy: the Singapore Malay eye study

Abstract: Purpose To describe the relationship of retinal vascular calibre with diabetes and diabetic retinopathy in an Asian population. Methods A total of 3280 (78.7% response) subjects, aged 40-80 years, of Malay ethnicity residing in Singapore participated in this population-based, cross-sectional study. Retinal vascular calibre was measured and summarized using a validated computer programme from digital retinal photographs. Diabetic retinopathy signs were graded from photographs using the modified Airlie House cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 28 publications
7
43
0
Order By: Relevance
“…16 This may be explained by a reduced retinal blood passage time due to shunt vessels, 17 by a decreased oxygen diffusion through the diabetic vessel wall resulting from a thickening of its basal membrane, or to a higher oxygen affinity of the hemoglobin A1c. However, in agreement with findings of increased vessel diameters 32,33 and blood flow 34 in diabetes, it also may indicate that blood flow regulation, even in rest, is at the upper limit of its control range in the patients to prevent tissue hypoxia. This also would explain why hardly any further increase of the SO 2 is seen in the patients during flicker stimulation.…”
Section: Discussionsupporting
confidence: 72%
“…16 This may be explained by a reduced retinal blood passage time due to shunt vessels, 17 by a decreased oxygen diffusion through the diabetic vessel wall resulting from a thickening of its basal membrane, or to a higher oxygen affinity of the hemoglobin A1c. However, in agreement with findings of increased vessel diameters 32,33 and blood flow 34 in diabetes, it also may indicate that blood flow regulation, even in rest, is at the upper limit of its control range in the patients to prevent tissue hypoxia. This also would explain why hardly any further increase of the SO 2 is seen in the patients during flicker stimulation.…”
Section: Discussionsupporting
confidence: 72%
“…Nonetheless, the experiments showed that the vascular geometry is indeed affected during the progression of diabetes, which is more or less in line with some of the previous findings [2,17,70]. The vessel widths, FD, venular angle to BC ratio, CRVE and CRAE were found to be important discriminative features of progression to DR. CRVE and CRAE observations are in line with the findings of Klein [71] and partly with [14,72,73]. These observations are linked possibly to the endothelial dysfunction, inflammatory changes, and hyperglycemia, all of which are factors involved in the pathogenesis of DR [74,75].…”
Section: Discussionsupporting
confidence: 75%
“…For example, our finding that persons with diabetes were more likely to have wider arterioles and venules than nondiabetic persons is compatible with many others with similar findings. 10,11,38 We also showed that people with diabetes had less tortuous arterioles than those without diabetes. We previously demonstrated that decreased retinal arteriolar tortuosity were associated with elevated blood pressure in our cohort, 21 and Witt and associates 39 found that decreased arteriolar tortuosity was associated with risk of ischemic heart disease mortality.…”
Section: Discussionmentioning
confidence: 70%